The Implementation of the Role-Playing Model to Enhance Students' Empathy in Understanding Social Conflicts in Social Studies Learning - Ngongo, Lidya; Sogen, Maria Magdalena Beatrice (SOSEARCH : Social Science Educational Research, 2025)
Social conflicts that frequently arise in society demand a learning approach that not only emphasizes cognitive aspects but also fosters the development of students’ empathy. In the context of Social Studies (IPS) education, understanding social conflict is crucial for enabling students to respond to differences wisely. This study aims to examine the effectiveness of implementing the role-playing learning model in enhancing students’ understanding and empathy toward the topic of social conflict. Using a descriptive qualitative approach with Classroom Action Research (CAR) design, the study was conducted in two cycles in Grade VIII at SMPK Sta. Maria Assumpta. Each cycle consisted of planning, action implementation, observation, and reflection stages. The results showed a significant improvement in both cognitive and affective aspects. The average student comprehension score increased from 66.3 (pre-action) to 84.7 at the end of the second cycle, while empathy scores rose from 60% to 85%. Learning through the role-playing model proved effective in encouraging critical thinking, understanding multiple perspectives in conflict, and developing students’ social sensitivity and empathy. These findings suggest that experiential learning approaches, such as role playing, are highly relevant for Social Studies education in shaping reflective and humanistic student character.